A tubular solid oxide fuel cell / electrolyzer block dense ceramic connector and its preparation method
By adopting a double-layer composite structure design and post-treatment process on the connector of the tubular solid oxide fuel cell/electrolytic cell, the problems of gas leakage and poor conductivity of the plasma sprayed connector are solved, and a ceramic connector with high density and high conductivity is achieved, which significantly improves the performance and stability of the battery.
Patent Information
- Application Number
- CN202310024164.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-09
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-01-09
AI Technical Summary
The existing plasma sprayed tube solid oxide fuel cell/electrolytic cell ceramic connectors have problems such as high gas leakage rate and poor coating conductivity, which cannot meet service needs.
Using the preparation method of double-layer composite structure design, the outer ceramic connector coating is prepared on the surface of the inner ceramic connector coating, and the metal ion salt solution is impregnated from the surface of the outer coating, and then heat treatment is carried out to promote the healing of defects in the coating and obtain a high-density structure.
It significantly improves the airtightness and conductivity of the ceramic connector, improves the performance and stability of the battery, and fully meets the service needs of the connector for airtightness and conductivity.
Smart Images

Figure CN116072903B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid oxide fuel cells / electrolyzers, and relates to a ceramic connector for a tubular solid oxide fuel cell, and in particular to a tubular solid oxide fuel cell / electrolyzer-like block-type dense ceramic connector and a preparation method thereof. Background Art
[0002] Solid oxide fuel cells / electrolyzers are important energy conversion devices with important applications in the fields of efficient power generation, water electrolysis to produce hydrogen, CO2 electrolysis, etc. Among them, compared with plate-structured batteries, tubular solid oxide fuel cells / electrolyzers have become the battery structure closest to commercial applications so far due to the characteristics of no need for high-temperature sealing, less thermal stress, simple assembly of single cells, and easy realization of high power. For example, Westinghouse Electric Company of the United States and Mitsubishi Heavy Industries of Japan have successfully developed tubular structure batteries. In addition, the Japanese patent JP5166517A published in 1993, the Chinese invention patent CN03114562.0 published in 2003, and the Chinese invention CN 201911136632.X published in 2020 all involve a single-tube battery structure with high voltage and low current output formed by connecting multiple single cells in series on a ceramic support or metal ceramic support tube. In this type of structural design, two adjacent batteries need to be connected in series by a connector with electronic conductivity. However, the working conditions of these connectors are harsh, one side of which is in a highly reducing fuel atmosphere, and the other side is in a highly oxidizing air or oxygen atmosphere, which results in such connectors not only needing to maintain the stability of structure and composition in the above atmosphere, but also requiring high density to isolate gas leakage, and also requiring high electronic conductivity to reduce the internal resistance of the battery. However, the tubular battery with a series structure has a complex structure, and a single high-temperature sintering molding process is difficult to meet its process requirements, and how to prepare a dense connector has become one of the important issues restricting tubular batteries with a series structure. At the same time, the battery tubes disclosed by Mitsubishi Heavy Industries of Japan (JP5166517A) and the Chinese invention patent (CN03114562.0) both mentioned the solution of preparing the connector using plasma spraying technology, and the Chinese invention patent 201911136632.X disclosed a solution for preparing the connector coating based on substrate preheating. However, ceramic coatings deposited based on plasma spraying technology usually have a large number of unbonded interfaces, vertical cracks, and pores. The three are connected in series to form a through gas channel, which makes the coating less airtight. When applied to tubular battery connectors, there will be gas leakage problems. Moreover, factors such as unbonded interfaces and vertical cracks between layers of the coating will lead to low electrical conductivity of the coating, which will bring greater ohmic impedance to the battery when used in connectors, thereby limiting the performance of the battery. Although substrate preheating can effectively increase the interlayer interface bonding of the coating, there are usually large internal stresses in the coating, which will lead to large vertical cracks, and the coating cannot be made completely dense. Moreover, it is difficult to preheat large long-tube batteries, and the expansion of the battery during the heating process will affect the preparation accuracy of the battery.Furthermore, for traditional coatings, if high-temperature sintering is used for direct treatment, due to the limitation of substrate shrinkage, if a dense structure is required, the treatment temperature usually required is higher than the sintering temperature of the corresponding block. However, too high a sintering temperature is usually not conducive to the preparation of other functional layers of the battery, and it is easy to cause deformation and cracking of the overall structure of the battery.
[0003] Therefore, in view of the problems of high gas leakage rate, poor coating conductivity and coating failure to meet service requirements of plasma nozzle solid oxide fuel cell / electrolyzer ceramic connectors, it is necessary to develop a new preparation method to produce block-like dense ceramic connectors based on plasma spraying. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention proposes a method for preparing a tubular solid oxide fuel cell / electrolyzer block-type dense ceramic connector based on plasma spraying. The connector adopts a double-layer composite structure design, obtains a high-density structure through a coating post-treatment process, and significantly improves the air tightness and electrical conductivity of the coating, thereby improving the performance and stability of the battery.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The present invention discloses a method for preparing a tubular solid oxide fuel cell / electrolyzer block-type dense ceramic connector, the method comprising the following steps:
[0007] S1. An inner ceramic interconnect coating with high electronic conductivity in a reducing atmosphere is first prepared between the porous fuel electrodes of a tubular solid oxide fuel cell / electrolyzer, and then an outer ceramic interconnect coating with high electronic conductivity in an oxidizing atmosphere is prepared on the surface of the inner ceramic interconnect coating, thereby constructing a double-layer ceramic interconnect coating to connect two adjacent batteries in series; the ceramic raw material selected for the inner ceramic interconnect coating is La 1-x Sr x TiO3(x:0.1~0.4), or La 1-x Sr x Ti 1-y Fe y O3(x:0.1~0.4,y=0.1-0.4), or La 1-x Sr x Ti 1-y Ni y O3 (x: 0.1-0.4, y = 0.1-0.2); the ceramic raw material selected for the outer ceramic interconnect coating is La 1-x Sr x MnO3(x:0.1~0.3), or Mn 2-x Co xO4 (x = 0.2-0.8), or La 1-x Sr x Co y Fe 1-y O3(x:0.2~0.5,y=0.1-0.3);
[0008] S2, impregnating the metal ion salt solution from the surface of the outer ceramic interconnect coating into the interconnect, and performing drying after impregnation;
[0009] S3. After drying, the connector coating is heated to decompose the infiltrated salt into corresponding oxides, thereby promoting the healing of defects in the coating through sintering, thereby obtaining a tubular solid oxide fuel cell / electrolyzer block-type dense ceramic connector.
[0010] Preferably, the ceramic raw material selected for the inner ceramic interconnect coating includes spherical La 0.7 Sr 0.3 TiO3 powder, spherical La 0.7 Sr 0.3 Ti 0.7 Fe 0.3 O3 powder, the particle size of the ceramic raw material is 30-60 μm.
[0011] Preferably, the ceramic raw material selected for the outer ceramic interconnect coating includes spherical La 0.8 Sr 0.2 MnO3 powder, spherical Mn 0.5 Co 1.5 O4 powder, spherical La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3 powder, the particle size of the ceramic raw material is 20-50 μm.
[0012] It should be noted that the connector of the quasi-sintered dense block coating prepared by the method of the present invention can completely eliminate the through-gas channels in the traditional plasma spray coating, has a sufficiently high density and airtightness, can effectively prevent the leakage and diffusion of fuel gas in the battery working environment, and can significantly improve the stability and life of the battery operation. The quasi-sintered dense block coating prepared by the method of the present invention has high stability in both reducing atmosphere and oxidizing atmosphere, and has high electronic conductivity in both the lateral and longitudinal directions. The interface bonding between the quasi-sintered dense block coating prepared by the method of the present invention and the anode overlap is strengthened during the infiltration and heat treatment process, thereby significantly reducing the interface resistance at the connector and the anode overlap. The ceramic materials used in the present invention are all ceramic materials that have very good thermal expansion matching with other functional layers such as battery electrolytes, so that the battery has good thermal matching stability during thermal cycling.
[0013] Preferably, the inner ceramic interconnect coating and the outer ceramic interconnect coating are both prepared by atmospheric or vacuum plasma spraying technology, and the thickness of the coating is 50 to 200 mm.
[0014] Preferably, the metal ion salt is nitrate or acetate, and its cation is Fe 3+ ,Co 3+ ,Ni 2+ ,Mn 4+ , Li + , Cu 2+ ,Bi 3+ When multiple cationic salts are used, the ratio of each ion is any ratio between 0-100%.
[0015] Preferably, the solvent of the metal ion salt solution is at least one of water, ethanol, ethylene glycol, or aqueous solutions of the above alcohols; and the concentration of the metal ion salt solution is 0.5-2.5 mol / L.
[0016] Preferably, the metal ion salt solution is infiltrated in an amount sufficient to fill all through pores, and the standard of measurement is until the coating cannot be infiltrated any more.
[0017] Preferably, the impregnation with the metal ion salt solution is performed by brushing.
[0018] Preferably, the drying temperature after impregnation with the metal ion salt solution is 80-120° C. and the drying time is 1-3 hours.
[0019] Preferably, the heat treatment is first heated to 400-500°C and kept warm for 0.5-1h, and then heated to 800-1250°C and kept warm for 2-10h; the atmosphere of the heat treatment is air, or argon, or nitrogen; the pressure is normal pressure, or a low pressure range from normal pressure to 2000Pa.
[0020] The present invention also provides a tubular solid oxide fuel cell / electrolyzer block-type dense ceramic connector prepared by the above-mentioned preparation method.
[0021] The tubular solid oxide fuel cell / electrolyzer block-type dense ceramic connector prepared by the above-mentioned preparation method has a dense microstructure and no through pores, and has high electronic conductivity in both the transverse and longitudinal directions under working conditions.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] Traditional plasma sprayed ceramic coatings contain through pores composed of a large number of unbonded interfaces, vertical cracks and pores. The through pores in the sprayed coating will reduce the conductivity of the coating and increase the battery operation impedance. The through pores will cause fuel gas leakage, which seriously affects the energy conversion efficiency of the battery. It not only poses a safety risk, but also significantly affects the service life of the battery. To this end, the present invention discloses a method for preparing a dense ceramic connector of a tubular solid oxide fuel cell / electrolyzer block based on a plasma spraying process. For a tubular solid oxide fuel cell / electrolyzer with a series structure, after preparing the fuel electrode, electrolyte and other structures, an inner ceramic connector with high electronic conductivity in a reducing atmosphere and an outer ceramic connector with high electronic conductivity in an oxidizing atmosphere are prepared respectively. The two adjacent cells are connected in series by a double-layer ceramic connector, and a metal ion salt solution is infiltrated from the surface of the prepared outer ceramic connector coating into the coating. After drying, the coating is heated to a certain temperature in a certain atmosphere for heat treatment, so that the infiltrated salt is decomposed into the corresponding oxide to promote the healing of the through pores in the coating after sintering, thereby obtaining a high-temperature sintered block-like dense ceramic connector coating. The present invention obtains a high-density block-like connector coating through the design of a double-layer connector and subsequent infiltration and heat treatment processes, which not only has high air tightness, but also has high conductivity and stability, thereby solving the problems of high gas leakage rate, poor coating conductivity, and coating failure to meet service requirements in existing plasma nozzle solid oxide fuel cell / electrolyzer ceramic connectors. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the structure of a tubular solid oxide fuel cell / electrolyzer;
[0025] Figure 2 The cross-section and surface morphology of the sprayed double-layer interconnect prepared in step (1) of Example 1 (a is the cross-section morphology of the interconnect in the sprayed state; b is the cross-section morphology of the interconnect after densification treatment);
[0026] Figure 3 The cross section and surface morphology of the connector coating after infiltration and heat treatment in Example 1 (a is the surface morphology of the connector in the sprayed state; b is the surface morphology of the connector after densification treatment).
[0027] Figure 1 Among them, 1-1 is a porous insulating ceramic support, 1-2 is a porous metal or metal ceramic support, 1-3 is a porous ceramic insulating layer, 1-4 is a porous fuel electrode, 1-5 is a dense electrolyte, 1-6 is a porous cathode, and 1-7 is a block-like dense ceramic connector. DETAILED DESCRIPTION
[0028] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0029] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0030] The solid oxide fuel cell / electrolyzer used in the present invention is a tubular solid oxide fuel cell / electrolyzer with a series structure (referred to as a series tubular cell), and its structure is as follows: Figure 1 a or Figure 1 b. Among them, Figure 1 a is a ceramic-supported series tubular cell (H. Tsukuda, A. Notomi, N. Histome, Application of plasma spraying to tubular-type solid oxide fuel cells production, Journal of Thermal Spray Technology, 9 (3) (2000) 364-368), Figure 1 b is a metal / metal ceramic supported series tubular battery (S.-L.Zhang, C.-X.Li, S.Liu, C.-J.Li, G.-J.Yang, P.-J.He, L.-L.Yun, B.Song, Y.-X.Xie, Thermally Sprayed Large Tubular Solid Oxide Fuel Cells and Its Stack: GeometryOptimization, Preparation, and Performance, Journal of Thermal Spray Technology 26(3)(2017)441-455.).
[0031] The substrate of the ceramic-supported series-connected tubular battery is a porous insulating ceramic support, on which a symmetrically arranged porous fuel electrode, a dense electrolyte and a porous cathode are sequentially arranged from bottom to top.
[0032] The substrate of the metal / metal ceramic supported series tubular battery is a porous metal or metal ceramic support body, on which a porous ceramic insulating layer is coated, and on which a symmetrically arranged porous fuel electrode, a dense electrolyte and a porous cathode are arranged in sequence from bottom to top.
[0033] Based on the above-mentioned series-connected tubular batteries, the present invention prepares a block-like dense ceramic connector between the porous fuel electrodes to connect two adjacent batteries in series. The height of the connector is equivalent to the total height of the porous fuel electrode and the dense electrolyte.
[0034] The following examples 1-7 specifically illustrate the method for preparing a block-like dense ceramic connector. It should be noted that these examples are preferred examples of the present invention and are used by those skilled in the art to understand the present invention, but the present invention is not limited to these examples.
[0035] Example 1 Preparation method of tubular solid oxide fuel cell / electrolyzer block dense ceramic connector
[0036] (1) Use spherical La with a particle size of 30-60 μm 0.7 Sr 0.3 TiO3 powder is used as raw material, atmospheric plasma spraying technology is used, and the F4 spray gun produced by Oerlikon Metco is used. The power is 36kW, Ar:H2=10:1, and the spraying distance is 100mm. On the basis of the fuel electrode, electrolyte and other functional layers of the series tubular battery, a 100μm coating (i.e., the inner ceramic connector coating) is sprayed. On this basis, a 20-50μm spherical La 0.8 Sr 0.2 MnO3 powder was used as raw material, and atmospheric plasma spraying technology was used to deposit a 100μm coating (i.e., the outer ceramic connector coating). The F4 spray gun produced by Oerlikon Metco was also used, with a power of 30kW, Ar:H2=15:1, and a spraying distance of 100mm to obtain a sprayed double-layer connector.
[0037] (2) Use high-purity water as solvent to prepare a 2 mol / L Co(NO3)3 solution, and use a brush coating method to coat the La 0.8 Sr 0.2 The surface of the MnO3 coating was infiltrated with Co(NO3)3 solution until the coating could no longer be infiltrated, and then dried at 100°C for 0.5h.
[0038] (3) The dried coating is placed in a high temperature furnace, heated to 450°C in an air atmosphere and normal pressure for 0.5 h, then heated to 1200°C for 2 h, and then cooled to room temperature to complete the preparation of the connector coating on the series tubular battery.
[0039] The cross-section and surface morphology of the spray-coated double-layer interconnect prepared in step (1) of Example 1 are as follows: Figure 2 As shown, from Figure 2 (a) It can be seen that the sprayed coating presents a layered structure as a whole, and there are a large number of unbonded interfaces and vertical cracks in the coating. Figure 2 (b) It can be seen that the surface of the sprayed connector presents a typical plasma sprayed ceramic coating morphology, and the presence of splashing particles and cracks can be observed. Figure 3 The cross section and surface morphology of the interconnect coating after infiltration and heat treatment are shown in FIG. Figure 3 As shown in (a), the layered structure and vertical cracks of the coating disappear, and the coating presents a dense sintered block fracture surface morphology. Although there are still a certain amount of pores in the coating, all the pores are tiny closed pores, such as Figure 3 As shown in (b), the coating surface is still rough, but the cracks disappear, the coating surface structure is dense, and obvious grains and grain boundaries are visible. The above results show that the microstructure of the connector coating prepared by this embodiment has reached a density close to that of a block state, has very high air tightness, and fully meets the service requirements of the connector for air tightness. Further conductivity test results show that under the test conditions of 800°C, one side of hydrogen and the other side of air, the obtained coating has a lateral apparent conductivity of 80S / cm and a longitudinal apparent conductivity of 42S / cm, which fully meets the service requirements of the battery.
[0040] Example 2 Preparation method of tubular solid oxide fuel cell / electrolyzer block dense ceramic connector
[0041] The preparation method is generally the same as that in Example 1, except that: step (2) uses a 2 mol / L Fe(NO3)3 solution; step (3) is first heated to 450°C and kept warm for 0.5 h, and then heated to 1250°C and kept warm for 2 h.
[0042] As in Example 1, the connector coating structure prepared in this example reaches a density close to that of a block, has very high air tightness, and fully meets the connector's service requirements for air tightness, and its electrical conductivity fully meets the battery's service requirements.
[0043] Example 3 Preparation method of tubular solid oxide fuel cell / electrolyzer block dense ceramic connector
[0044] The preparation method is generally the same as that in Example 1, except that: Step (2) is to prepare a 2 mol / L Bi(NO3)3 solution using ethylene glycol as solvent, and to apply the solution to the La 0.8 Sr 0.2 The surface of the MnO3 coating is infiltrated with Bi(NO3)3 solution until the coating can no longer be infiltrated, and then dried at 150°C for 0.5h; step (3) is to first heat to 450°C and keep it for 0.5h, and then heat to 1150°C and keep it for 2h.
[0045] As in Example 1, the connector coating structure prepared in this example reaches a density close to that of a block, has very high air tightness, and fully meets the connector's service requirements for air tightness, and its electrical conductivity fully meets the battery's service requirements.
[0046] Example 4 Preparation method of tubular solid oxide fuel cell / electrolyzer block dense ceramic connector
[0047] The preparation method is generally the same as that in Example 1, except that: Step (2) is to prepare a 1.5 mol / L mixed solution of Co(NO3)3 and Fe(NO3)3 using high-purity water as solvent, with a molar ratio of Co to Fe of 1:1, and to apply the mixture on the La 0.8 Sr 0.2 The mixed solution was infiltrated into the MnO3 coating surface until it could no longer be infiltrated, and then dried at 100°C for 0.5h.
[0048] As in Example 1, the connector coating structure prepared in this example reaches a density close to that of a block, has very high air tightness, and fully meets the connector's service requirements for air tightness, and its electrical conductivity fully meets the battery's service requirements.
[0049] Example 5 Preparation method of tubular solid oxide fuel cell / electrolyzer block dense ceramic connector
[0050] The preparation method is generally the same as in Example 1, except that: Step (1) is to prepare spherical La with a particle size of 30-60 μm. 0.7 Sr 0.3 Ti 0.7 Fe 0.3 O3 powder is used as raw material to prepare the inner ceramic interconnect coating, and spherical Mn 0.5 Co 1.5 O4 powder is used as raw material to prepare the outer ceramic interconnect coating; step (3) is to first heat to 450°C and keep it for 0.5h, and then heat to 1150°C and keep it for 2h.
[0051] As in Example 1, the connector coating structure prepared in this example reaches a density close to that of a block, has very high air tightness, and fully meets the connector's service requirements for air tightness, and its electrical conductivity fully meets the battery's service requirements.
[0052] Example 6 Preparation method of tubular solid oxide fuel cell / electrolyzer block dense ceramic connector
[0053] The preparation method is generally the same as that of Example 1, except that: Step (1) is to prepare spherical La with a particle size of 30-60 μm. 0.7 Sr 0.3Ti 0.7 Fe 0.3 O3 powder is used as raw material to prepare the inner ceramic interconnect coating, and spherical Mn 0.5 Co 1.5 O4 powder is used as raw material to prepare the outer ceramic interconnect coating; step (2) is to brush 1.5 mol / L Co(NO3)3 solution; step (3) is to first heat to 450°C and keep it for 0.5h, and then heat to 1150°C and keep it for 2h.
[0054] As in Example 1, the connector coating structure prepared in this example reaches a density close to that of a block, has very high air tightness, and fully meets the connector's service requirements for air tightness, and its electrical conductivity fully meets the battery's service requirements.
[0055] Example 7 Preparation method of tubular solid oxide fuel cell / electrolyzer block dense ceramic connector
[0056] The preparation method is generally the same as that of Example 1, except that: Step (1) is to prepare spherical La with a particle size of 30-60 μm. 0.7 Sr 0.3 Ti 0.7 Fe 0.3 O3 powder is used as raw material to prepare the inner ceramic interconnect coating, and spherical La with a particle size of 20-50μm is used as raw material. 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3 powder is used as raw material to prepare the outer ceramic interconnect coating; step (2) is to brush on 1.5 mol / L Co(NO3)3 solution.
[0057] As in Example 1, the connector coating structure prepared in this example reaches a density close to that of a block, has very high air tightness, and fully meets the connector's service requirements for air tightness, and its electrical conductivity fully meets the battery's service requirements.
[0058] It can be seen from Examples 1-7 that the high-density block-like connector coating obtained by the method of the present invention not only has high air tightness, but also has high electrical conductivity and stability, thereby solving the problems of high gas leakage rate, poor coating conductivity and inability of the coating to meet service requirements in the existing plasma nozzle solid oxide fuel cell / electrolyzer ceramic connector.
[0059] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A method for preparing a tubular solid oxide fuel cell / electrolyzer block dense ceramic connector, characterized in that: The following steps are involved: S1. An inner ceramic interconnect coating with high electronic conductivity in a reducing atmosphere is first prepared between the porous fuel electrodes of a tubular solid oxide fuel cell / electrolyzer, and then an outer ceramic interconnect coating with high electronic conductivity in an oxidizing atmosphere is prepared on the surface of the inner ceramic interconnect coating, thereby constructing a double-layer ceramic interconnect coating to connect two adjacent batteries in series; the ceramic raw material selected for the inner ceramic interconnect coating is La 1-x Sr x TiO3,x:0.1~0.4, or La 1-x Sr x Ti 1-y Fe y O3,x:0.1~0.4,y=0.1-0.4, or La 1-x Sr x Ti 1-y Ni y O3, x: 0.1~0.4, y=0.1-0.2; the ceramic raw material selected for the outer ceramic interconnect coating is La 1-x Sr x MnO3,x:0.1~0.3, or Mn 2- x Co x O4, x = 0.2-0.8, or La 1-x Sr x Co y Fe 1-y O3, x: 0.2~0.5, y=0.1-0.3; S2, impregnating the metal ion salt solution from the surface of the outer ceramic interconnect coating into the interconnect, and performing drying after impregnation; S3. After drying, the connector coating is heated to decompose the infiltrated salt into corresponding oxides, thereby promoting the healing of defects in the coating through sintering, thereby obtaining a tubular solid oxide fuel cell / electrolyzer block-type dense ceramic connector.
2. The method for preparing a tubular solid oxide fuel cell / electrolyzer block dense ceramic connector according to claim 1, characterized in that: The ceramic raw materials selected for the inner ceramic interconnect coating include spherical La 0.7 Sr 0.3 TiO3 powder, spherical La 0.7 Sr 0.3 Ti 0.7 Fe 0.3 O3 powder, the particle size of the ceramic raw material is 30-60 μm.
3. The method for preparing a tubular solid oxide fuel cell / electrolyzer block dense ceramic connector according to claim 1, characterized in that: The ceramic raw materials selected for the outer ceramic interconnect coating include spherical La 0.8 Sr 0.2 MnO3 powder, spherical Mn 0.5 Co 1.5 O4 powder, spherical La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3 powder, the particle size of the ceramic raw material is 20-50 μm.
4. The method for preparing a tubular solid oxide fuel cell / electrolyzer block dense ceramic connector according to claim 1, characterized in that: The inner ceramic interconnect coating and the outer ceramic interconnect coating are both prepared by atmospheric or vacuum plasma spraying technology, and the thickness of the coating is 50 to 200 mm.
5. The method for preparing a tubular solid oxide fuel cell / electrolyzer block dense ceramic connector according to claim 1, characterized in that: The metal ion salt is nitrate or acetate, and its cation is Fe 3+ ,Co 3+ ,Ni 2 + ,Mn 4+ , Li + , Cu 2+ ,Bi 3+ At least one of .
6. The method for preparing a tubular solid oxide fuel cell / electrolyzer block dense ceramic connector according to claim 1, characterized in that: The solvent of the metal ion salt solution is at least one of water, ethanol, ethylene glycol, or aqueous solutions of the above alcohols; the concentration of the metal ion salt solution is 0.5-2.5 mol / L.
7. The method for preparing a tubular solid oxide fuel cell / electrolyzer block dense ceramic connector according to claim 1, characterized in that: The amount of metal ion salt solution impregnated is to fill all through pores, and the standard of measurement is until the coating cannot be impregnated.
8. The method for preparing a tubular solid oxide fuel cell / electrolyzer block dense ceramic connector according to claim 1, characterized in that: The drying temperature after impregnation with the metal ion salt solution is 80-120° C. and the drying time is 1-3 hours.
9. The method for preparing a tubular solid oxide fuel cell / electrolyzer block dense ceramic connector according to claim 1, characterized in that: The heat treatment is first heated to 400-500°C and kept warm for 0.5-1h, and then heated to 800-1250°C and kept warm for 2-10h; the atmosphere of the heat treatment is air, or argon, or nitrogen; the pressure is normal pressure, or a low pressure range from normal pressure to 2000Pa.
10. A tubular solid oxide fuel cell / electrolyzer block-type dense ceramic interconnect prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Fabrication method of a tubular solid oxide fuel cell with double-layer connected electrodes
CN110890570B
Single-cell structure of tube-like high-temperature solid oxide fuel battery
CN1209844C
Hoosu
JP1976066517A
Composite ceramic connector for tubular solid oxide fuel cells and its preparation method
CN102299354A
Anode-supported solid oxide fuel cell, cell stack and preparation method thereof
CN102651480A